Evaluation of the eosin-5-maleimide flow cytometric test and other screening tests in the diagnosis of hereditary spherocytosis - Mothi, Hemasha (University of the Free State, 2020)
Background: Hereditary spherocytosis (HS) is a genetically determined haemolytic anaemia characterised by the spherical shape of affected red blood cells. With limited confirmatory tests currently available in South Africa, the diagnosis of HS is reliant on the clinical presentation and screening tests. Objectives: The aim of this study was to compare the sensitivity and specificity of three screening tests: flow osmotic fragility test (FOFT), cryohaemolysis test (CHT) and the eosin-5-maleimide binding test (EMA-binding test) in diagnosing hereditary spherocytosis (HS). Method: All three tests were performed on 18 subjects with confirmed HS. The negative control group was comprised of 10 subjects with haemolysis and spherocytosis, and either a positive direct antiglobulin test (DAT) or normal red cell membrane studies. The tests were also performed on samples submitted for cases of suspected HS during the study period. Results: The EMA-binding test demonstrated superior sensitivity (88.9%) compared to the CHT (61.1%) and the FOFT (38.8%). The EMA-binding test specificity (90.0%) was equal to that of the FOFT and superior to the CHT (50%). Combined sensitivities and specificities for EMA-binding test and CHT, EMAbinding test and FOFT, and CHT and FOFT, were 100% and 33.3%, 94.4% and 80.0% and 88.9% and 50.0%, respectively. Conclusion: EMA-binding test is the best screening test for cases of suspected HS. If there is a high clinical index of suspicion with a negative EMA-binding test, the CHT is recommended as a second screening test.
Keywords: Dissertation (M.Med Sc. (Haematology and Cell Biology))--University of the Free State, 2020; Hereditary spherocytosis; Eosin-5-maleimide; Flow osmotic fragility; Cryohaemolysis; Screening test; Red cell membrane; South Africa